Evaluasi dan Perancangan Ulang Antarmuka e-Learning SMK Negeri 1 Cerme menggunakan Metode Goal Directed Design (GDD) - Nur Fitriani; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
SMK Negeri 1 Cerme is one of the SMKN in the Gresik Regency, East Java, which has 8 departments. In this research activity, respondents involved as many as 20 people in questionnaire respons and 5 people in testing the task scenario and interviews. Preliminary data obtained from this research activity shows that e-learning users, namely students of SMKN 1 Cerme, still experience difficulties, both from the language used and the appearance that is less attractive and informative. This research purpose to redesign the e-learning of SMKN 1 Cerme using the Goal Directed Design (GDD) method. The GGD method is a method that focuses on the goals of the user, in the GDD method there are 6 stages, research, modeling, requirements, framework, refinement and support. However, this research only reached the refinement stage because the researchers did not go to the development or support stage. The evaluation process before and after designing uses the Usability Testing method. Usability Testing is a method that focuses on the level of system usability by users, namely students of SMKN 1 Cerme Gresik. Usability Testing used in this study is usability testing ISO 9241-11. From the user side, there are positive and negative responses in its implementation, the icons used do not represent functions, the language used is not informative, the layout on the display is not neat so that it confuses the user in using it. The addition of a search feature that makes it easy for users to choose colors that represent SMKN 1 Cerme.